The Correlation Among Gender, Languange Learning Strategies, and English Achievment of English Departement Students of Tarbiyah Faculty - Maulina Maulina (Universitas Cokroaminoto Palopo, 2015)
This was a correlational research with two predictors and one criterion. 103 students (both successful and unsuccessful male and female students) were involved in this research. The data obtained through SILL by Oxford (1990) and students’ English achievement based on gender were analyzed by using descriptive statistics and inferential statistics through SPSS program version 20.0. The findings, first of all showed that there was a significant correlation between gender and English achievement where r = 0.924 and p = 0.000   = 0.05. Second, there was not any significant correlation between LLSs and English achievement where r = 0.202 and p = 0.083   = 0.05. Third, there was not any significant correlation between successful gender and their LLSs where r = 0.222 and p = 0.056   = 0.05 but there was a significant correlation between unsuccessful gender and their LLSs where r = - 0.376 and p = 0.049   = 0.05. Fourth, There was a significant correlation between gender and LLSs used simultaneously with English achievement where r = 0.264 and p = 0.04   = 0.05.